Remittance Inflows to Nepal: Economic Impact and Policy Options - Pant, Bhubanesh (NRB Economic Review, 2006)
Remittances are generally thought to contribute to savings and investments thus leading to economic growth. In 2004, officially recorded remittances flows to developing countries were greater than US 125 billion. The rise in remittances, that are less affected by economic cycles in the recipient country, are taking place at a time of declining official development assistance which adds more significance to the remittance debate and research. The various uses of the remitted funds vary in their potential to reduce poverty and create economic security for the household and community. In Nepal’s case, in more recent years, remittances have been playing a pivotal role in the country’s economic development by relaxing the foreign exchange constraints and strengthening the balance of payments, among others. Although a gamut of policy measures have been taken by the concerned authorities for encouraging remittances through the banking channel, more needs to be done.